Concept and behaviour of miniature bar-typed structural fuses with eccentricity. (March 2020) - Guan, Dongzhi; Yang, Sen; Wang, Zeqing; Jia, Liang-Jiu; Guo, Zhengxing; Ge, Hanbin
Abstract: Miniature structural fuses made from round steel bars, have been increasingly investigated and applied because they can be easily replaced and have a low cost. In this paper, a miniature bar-typed structural fuse with eccentricity (MBFE) was proposed. The yielding portion in the central energy dissipation core was made into a circular segment cross-section, leading to an initial eccentricity. A total of 6 specimens were tested under reversal cyclic loadings with the test parameters, i.e., the eccentricity, the cross-sectional shapes of the yielding portions and the existence of Teflon pads. A simplified analytical model was developed to analyze the MBFE. The results show that the specimens exhibit a satisfactory seismic performance. The initial eccentricity leads to slight fluctuations in the hysteretic curves when the MBFE is under compression and increments in the compressive strength of the MBFE. The simplified analytical model, considering the eccentricity effect, can be adopted to estimate the envelope curve of the MBFE. Highlights: A novel miniature bar-typed structural fuse with eccentricity (MBFE) was investigated. The initial eccentricity leads to extra moment when the MBFE is loaded longitudinally. The MBFE has satisfactory seismic performance with some slight fluctuations in the compressive halves of hysteretic curves. The proposed theoretical model considering the initial eccentricity matches well with the experimental results.